PENGEMBANGAN APLIKASI PEMBELAJARAN MENULIS TEKS EKSPLANASI SISWA KELAS V SEKOLAH DASAR - Muhammad Rizal; Dadan Djuanda; Prana Dwija Iswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an Android application-based learning media for writing explanatory texts for elementary school students. This media was developed in response to students' weak ability to compose explanatory texts according to the rules, which is caused by limited understanding of text structure and lack of internal motivation to write. The research method used is Design and Development (D&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The product developed is an Android application using Smart Apps Creator, equipped with materials, learning videos, quizzes, writing features, and an automatic correction system. The validation results by material experts showed a feasibility score of 85.33% and media experts 96.36%, which is included in the very feasible category. The trial on students showed very practical results, with a score of 84.95% in small groups and 88.82% in large groups. This application is declared feasible and practical for use in learning to write explanatory texts in grade V of elementary school, and is able to improve students' understanding of text structure and writing skills independently and interactively.